2019
DOI: 10.3390/genes10120964
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA from PVT1 Exon 9 Is Overexpressed in Prostate Cancer and Induces Malignant Transformation and Castration Resistance in Prostate Epithelial Cells

Abstract: Prostate cancer (PCa) is the most common non-cutaneous cancer and second leading cause of cancer-related death for men in the United States. The nonprotein coding gene locus plasmacytoma variant translocation 1 (PVT1) is located at 8q24 and is dysregulated in different cancers. PVT1 gives rise to several alternatively spliced transcripts and microRNAs. There are at least twelve exons of PVT1, which make separate transcripts, and likely have different functions. Here, we demonstrate that PVT1 exon 9 is signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…This observation was made from comparing the relative expression of PVT1 exons in different cell lines derived from men of different ethnic and racial backgrounds. In a more recent study by the Ogunwobi laboratory, PVT1 exon 9 was found to be upregulated in prostate cancer tissues when compared to normal prostate tissues (95). This is consistent with previous studies on the expression of PVT1 exon 9 in prostate cancer cell lines (96).…”
Section: Pvt1 In Prostate Cancersupporting
confidence: 90%
“…This observation was made from comparing the relative expression of PVT1 exons in different cell lines derived from men of different ethnic and racial backgrounds. In a more recent study by the Ogunwobi laboratory, PVT1 exon 9 was found to be upregulated in prostate cancer tissues when compared to normal prostate tissues (95). This is consistent with previous studies on the expression of PVT1 exon 9 in prostate cancer cell lines (96).…”
Section: Pvt1 In Prostate Cancersupporting
confidence: 90%
“…Plasmacytoma Variant Translocation 1 (PVT1) is a long non-protein-coding gene, located at chromosome 8q24 and contains approximately twelve exons and encodes a cluster of six microRNAs ( Ilboudo et al 2015 ; Colombo et al 2015 ). Several studies have reported that PVT1 plays a role in tumorigenesis, proliferation, apoptosis, cell cycle progression, migration, and invasion ( Chen et al 2018a ; Derderian et al 2019; He et al 2019 ; Pal et al 2019 ; Onagoruwa et al 2020 ). Aberrations of PVT1 are associated with different malignancies including cervical cancer, bladder cancer, colorectal cancer, gastric cancer, breast cancer, hepatocellular carcinoma, lung cancer, and breast cancer ( Wan et al 2016 ; Iden et al 2016 ; Chen et al 2018b ; Tang et al 2018 ; He et al 2019 ; Yu et al 2019 ).…”
mentioning
confidence: 99%
“…Of note, the PVT1-217 transcript is the most abundant in the gastrointestinal tract mucosa [ 115 ]. Furthermore, PVT1 expression is elevated in multiple cancer types including lung [ 129 ], prostate [ 130 ], cervical [ 131 ], and colon [ 132 ]. Possible functional roles for PVT1 are mediated by miRNAs, and competing endogenous RNA (ceRNA), involving regulation of gene activity through C-MYC activation [ 115 , 125 , 133 ].…”
Section: The Role Of Pvt1 In the Diagnosis Treatment And Prognosimentioning
confidence: 99%